Effect of the electronic structure on the robustness of ruthenium(ii) bis-phenanthroline compounds for photodissociation of the co-ligand: synthesis, structural characterization, and density functional theory study. (10th March 2021) - Deshpande, Megha S.; Morajkar, Sudesh M.; Srinivasan, Bikshandarkoil R.; Ahirwar, Mini Bharati; Deshmukh, Milind M.
Abstract : Photodissociation of co-ligand in cis -[Ru(phen)2 (L)2 ](PF6 )2 (phen = 1, 10-phenanthroline, L = isoquinoline 1 ; phthalazine 2 ), upon blue light irradiation was investigated via both experimental and DFT studies. Abstract : Distorted octahedral ruthenium(ii ) bis-phenanthroline compounds of the type cis -[Ru(phen)2 (L)2 ](PF6 )2 (L = isoquinoline 1 ; phthalazine 2 ) were synthesized and their photochemistry was investigated. The photodissociation of the monodentate N-heterocyclic co-ligands upon blue light irradiation ( λ irr = 470 nm) occurs much more readily in 1 than in 2 with the first ligand dissociating faster than the second ligand. The density functional theory (DFT) calculations were performed to investigate geometries of the 3 MLCT, 3 TS, and dissociative 3 MC states and the triplet potential energy surfaces. DFT and time-dependent DFT (TD-DFT) calculations reveal a smaller 3 MLCT- 3 MC energy gap for 1 (0.025 eV) than in 2 (0.090 eV) suggesting the faster dissociation of the first co-ligand in both 1 and 2 . On the other hand, the 3 MLCT- 3 MC energy gap is moderately larger for the monochloro-substituted photoproducts 1a (0.389 eV) and 2a (0.396 eV), leading to the conclusion that the second co-ligand dissociation is slower in both 1a and 2a . This is also in agreement with the observed values of quantum yields. Molecular orbital analysis along the triplet potential energy surface scan for Ru–N(co-ligand) bond stretching suggests that the lower energy singly occupied molecular orbital (SOMO1 ) of 3 MLCT, comprised of a dπ orbital of Ru with little contribution of π orbital of the co-ligand, does not change much when Ru–N bond stretches to reach 3 MC. The higher-energy SOMO2 of the 3 MLCT state is mostly phenanthroline based π* orbital. Upon stretching the Ru–N distance, the π* orbital of phenanthroline in the 3 MLCT state and dσ * orbital of the dissociative 3 MC state are seen to be mixing in an antibonding fashion especially after transition state ( 3 TS). This mixing of the dσ * orbital with the π * orbital is one of the important factors favoring the release of the N-heterocyclic co-ligand to give photodissociation products.